Carbon Supply and Photoacclimation Cross Talk in the Green Alga Chlamydomonas reinhardtii. Issue 3 (16th September 2016) - Polukhina, Iryna; Fristedt, Rikard; Dinc, Emine; Cardol, Pierre; Croce, Roberta
Abstract : High-light acclimation strategies of Chlamydomonas reinhardtii cells grown in different carbon supply regimes show the high plasticity of the photosynthetic apparatus. Abstract: Photosynthetic organisms are exposed to drastic changes in light conditions, which can affect their photosynthetic efficiency and induce photodamage. To face these changes, they have developed a series of acclimation mechanisms. In this work, we have studied the acclimation strategies of Chlamydomonas reinhardtii, a model green alga that can grow using various carbon sources and is thus an excellent system in which to study photosynthesis. Like other photosynthetic algae, it has evolved inducible mechanisms to adapt to conditions where carbon supply is limiting. We have analyzed how the carbon availability influences the composition and organization of the photosynthetic apparatus and the capacity of the cells to acclimate to different light conditions. Using electron microscopy, biochemical, and fluorescence measurements, we show that differences in CO2 availability not only have a strong effect on the induction of the carbon-concentrating mechanisms but also change the acclimation strategy of the cells to light. For example, while cells in limiting CO2 maintain a large antenna even in high light and switch on energy-dissipative mechanisms, cells in high CO2 reduce the amount of pigments per cell and the antenna size. Our results show the high plasticity of the photosynthetic apparatus of C. reinhardtii . This alga is able to use various photoacclimation strategies, and the choice of which to activate strongly depends on the carbon availability.